Recombination events during integration of transfected DNA into normal human cells. - Murnane, J P (1990)
The mechanisms of recombination responsible for random integration of transfected DNA into the genome of normal human cells have been investigated by analysis of plasmid-cell DNA junctions. Cell clones containing integrated plasmid sequences were selected by morphological transformation of primary human fibroblasts after transfection with a plasmid containing simian virus 40 sequences. Nucleotide sequence analysis of the plasmid-cell DNA junctions was performed on cloned DNA fragments containing the integration sites from two of these cell clones. Polymerase chain reaction was then performed with human cell DNA from primary fibroblasts to isolate the cell DNA from the same sites before plasmid integration. Comparison of the sequences at the plasmid-cell DNA junctions with those of both the original plasmid and the cell DNA demonstrated short sequence similarities and additional nucleotides, typical of nonhomologous recombination. Evidence of short deletions in the cell DNA at the plasmid integration sites suggests that integration occurred by a mechanism similar to that used for repair of spontaneous or gamma ray-induced strand breaks. Plasmid integration occurred within nonrepetitive cell DNA with no major rearrangements, although rearrangements of the cell DNA at the integration site occurred in one of the clones after integration.